Multifunctional Islet Transplantation Hydrogel Encapsulating A20 High-Expressing Islets - Bai X; Pei Q; Pu C; Chen Y; He S; Wang B (Dove Medical Press, 2020)
Xue Bai1,2 *,* Qilin Pei3 *,* Chunyi Pu,1,2 Yi Chen,1,2 Sirong He,1,2 Bin Wang3 1Department of Immunology, College of Basic Medicine, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Chongqing Key Laboratory of Basic and Translational Research of Tumor Immunology, Chongqing Medical University, Chongqing 400016, People’s Republic of China; 3Institute of Life Sciences, Chongqing Medical University, Chongqing 400016, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sirong He; Bin Wang Email hesirong@cqmu.edu.cn; bwang@cqmu.edu.cnAbstract: Islet transplantation is regarded as the most promising treatment for type 1 diabetes (T1D). However, the function of grafted islet could be damaged on account of transplant rejection and/or hypoxia several years later after transplantation. We proposed a hypothetical functionalized hydrogel model, which encapsulates sufficient A20 high-expressing islets and supporting cells, and performs as a drug release system releasing immunosuppressants and growth factors, to improve the outcome of pancreatic islet transplantation. Once injected in vivo, the hydrogel can gel and offer a robust mechanical structure for the A20 high-expressing islets and supporting cells. The natural biomaterials (eg, heparin) added into the hydrogel provide adhesive sites for islets to promote islets’ survival. Furthermore, the hydrogel encapsulates various supporting cells, which can facilitate the vascularization and/or prevent the immune system attacking the islet graft. Based on the previous studies that generally applied one or two combined strategies to protect the function of islet graft, we designed this hypothetical multifunctional encapsulation hydrogel model with various functions. We hypothesized that the islet graft could survive and maintain its function for a longer time in vivo compared with naked islets. This hypothetical model has a limitation in terms of clinical application. Future development work will focus on verifying the function and safety of this hypothetical islet transplantation hydrogel model in vitro and in vivo.Keywords: islet transplantation, hydrogel, T1D, encapsulation, biomaterials